Preparation Dye- Sensitized Solar Cells Based on ZnO Films and Shami Berries Natural Dye - Amer, Ola Shaher; Alghoraibi, Ibrahim (Iraqi Journal of Science, 2025)
The photoelectrode of the dye-sensitized solar cells was fabricated by sensitizing ZnO with a natural extract of Shami berries with different solvents. The working electrode of ZnO nanoparticles was synthesized using the sol-gel and dip-coating method and deposited onto ITO substrates using zinc acetate dihydrate as a precursor. The study investigated the effect of solvent type (methanol and ethanol), substrate withdrawal speed (1mm/s and 5mm/s), and catalyst agent (Triethanolamine (TEA) and Monoethanolamine (MEA)) on photoconversion in the dye-sensitized solar cell. An atomic force microscope examined the nanostructure of the prepared film, indicating nanoparticle sizes in the range from 48 to 105 nm. The optical properties analyzed with a UV-Vis spectrophotometer (wavelength: 300-800 nm) showed a band gap energy of 3.26 eV for the ZnO thin films sensitized with methanol as solvent, withdrawal speed of 1mm/s and TEA as the catalyst agent. The band gap energy for Shami berries extract with acidified ethanol as the solvent was found to be 1.7eV. Cyclic voltammetry estimated the energy levels of the dye’s highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) at -5.2 eV and -3.5 eV, respectively. Additionally, the study evaluated the efficiency of dye-sensitized solar cells under optimal experimental conditions. The DSSC utilizing Shami berries extract with acidified ethanol had the highest photoconversion efficiency (η) of 0.79%.